Urgent Care Staffing Assignments - Hutchison, Scott (My University, 2024)
This Executive Summary detailing a quality improvement project is a component of the DNP program.
Keywords: urgent care; staffing assignments; clinical roles; clinic efficiency; staffing patterns; workload distribution; patient wait times; healthcare management